Melatonin/PGC1A/UCP1 promotes tumor slimming and represses tumor progression by initiating autophagy and lipid browning. Issue 4 (13th September 2019) - Xiao, Wen; Xiong, Zhiyong; Xiong, Wei; Yuan, Changfei; Xiao, Haibing; Ruan, Hailong; Song, Zhengshuai; Wang, Cheng; Bao, Lin; Cao, Qi; Wang, Keshan; Cheng, Gong; et al.
Abstract: Metabolic adaptations are emerging hallmarks of cancer progression and cellular transformation. Clear cell renal cell carcinoma (ccRCC) is a metabolic disease defined histologically by lipid accumulation and lipid storage, which promote tumor cell survival; however, the significance of eliminating the lipid remains unclear. Here, we demonstrate that melatonin activates transcriptional coactivator peroxisome proliferator‐activated receptor gamma coactivator 1A (PGC1A) and uncoupling protein 1 (UCP1)‐dependent lipid autophagy and a lipid browning program to elicit a catabolic state called "tumor slimming, " thus suppressing tumor progression. Metabolic coregulator data analysis revealed that PGC1A expression was decreased in ccRCC tissues versus normal tissues, and poor patient outcome was associated with lower expression of PGC1A in The Cancer Genome Atlas (TCGA‐KIRC). PGC1A was downregulated in ccRCC and associated with disease progression. Restoration of PGC1A expression by melatonin in ccRCC cells significantly repressed tumor progression and eliminated the abnormal lipid deposits. Furthermore, a phenomenon called "tumor slimming" was observed, in which tumor cell volume was reduced and lipid droplets transformed into tiny pieces. Additional studies indicated that melatonin promoted "tumor slimming" and suppressed ccRCC progression through PGC1A/UCP1‐mediated autophagy and lipid browning. During this process, autophagy and lipid browning eliminate lipid deposits without providing energy. These studies demonstrate that the novel "tumor slimming" pathway mediated by melatonin/PGC1A/UCP1 exhibits prognostic potential in ccRCC, thus revealing the significance of monitoring and manipulating this pathway for cancer therapy.